The Effectiveness of Discovery Learning Model using Audio-Visual Media (Journal of Primary Education, 2019)
The learning model is one of the factors that influence student learning outcomes. The purpose of this study was to determine the effectiveness of learning outcomes based on students' motivation in thematic learning with The Discovery Learning Model assisted by audio-visual media with the theme of Our Friends Environment in elementary schools. This type of research is quantitative with quasi-experimental research (quasi-experiment). This study uses a pre-test – post-test nonequivalent control group design with two class research objects consisting of a control class (Public Elementary School Kalipancur 2, Semarang) and an experimental class (Public Elementary School Purwoyoso 4, Semarang). The sample consisted of 72 students. This data collection technique uses N-Gain analysis. The results of this study are an increase in learning outcomes based on motivation significantly. Obtained an average increase in learning outcomes of 87.4% in the very good category. The average skill of 75.8% is in the very good category. An average motivation of 86% is in the very good category. The average N-Gain test of 0.602 is in the medium category. The conclusion of this research is an increase in student learning outcomes after participating in thematic learning with The Discovery Learning Model assisted by audio-visual media. Motivation accompanies an increase in student learning outcomes.